Rapid Response of a Sand‐Dominated River to Installation and Removal of a Temporary Run‐of‐the‐River Dam. (8th October 2014) - Costigan, K. H.; Ruffing, C. M.; Perkin, J. S.; Daniels, M. D.
Abstract: Run‐of‐the‐river dams (RORDs) comprise the vast majority of dams on river systems and are commonly removed as a part of stream restoration strategies. Although these dams are routinely removed, few studies have documented the geomorphological responses of sand‐bed rivers to the removal of RORDs. We examined the response of a large sand‐bed river located in South‐Central Kansas, USA, to the installation and removal of a dam that is installed annually for seasonal recreational purposes. Channel adjustments were tracked using cross‐sections sampled over the course of 7 months as the dam was installed and subsequently removed. Multivariate spatiotemporal analysis revealed emergence of channel stability when the dam was in place for most cross‐sections, except for those immediately adjacent to or at great distances from the dam. Our results provide an approximation for how sand‐bed rivers respond to RORD construction and removal and are useful for guiding management decisions involving preservation or restoration of connectivity. Results of this study suggest that sand‐bed rivers are resilient and recover quickly when transient RORDs are removed. Copyright © 2014 John Wiley & Sons, Ltd.